What on Earth is a Ruling Party in a Multiparty Democracy? Musings and Ruminations of an Armchair Critic - Kashoki, E.; Kashoki, E. (Gadsden Publishers, 2014)
The primary objective of What on Earth is a Ruling Party in a Multiparty Democracy? is to provoke thought and thereby stimulate debate. To this end, provocatively, this collection of topical issues ranges from 'The place of the miniskirt in sociocultural development' to 'Which citizen in Zambia should not take part in (partisan) politics?' The Author, Mubanga E Kashoki, is a Professor of African Languages at the institute of Economic and Social Research in the University of Zambia.